On Examining Communicative Tasks in Second Language Acquistion - Golda J. Tulung (TEFLIN Journal: A publication on the teaching and learning of English, 2008)
Studies of second language acquisition (SLA) suggest that communicative tasks can provide the conditions and processes that may facilitate second language learning.ÃÂ  Attempting to understand how communicative tasks may promote SLA, this article examines communicative tasks in second language learning by (1) defining and categorizing tasks, (2) providing theoretical rationale for tasks with respect to meaningful oral exchanges or interaction generated from tasks, and (3) discussing how the linguistic and interactional characteristics of the exchanges may differentially promote learners language acquisition.